2016
DOI: 10.4274/tjh.2014.0378
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Epidemiology of Bloodstream Infections and Resistance in Hematopoietic Stem Cell Transplantation Recipients

Abstract: Objective:Patients receiving hematopoietic stem cell transplantation (HSCT) are exposed to highly immunosuppressive conditions and bloodstream infections (BSIs) are one of the most common major complications within this period. Our aim, in this study, was to evaluate the epidemiology of BSIs in these patients retrospectively.Materials and Methods:The epidemiological properties of 312 patients with HSCT were retrospectively evaluated.Results:A total of 312 patients, followed between 2000 and 2011, who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Reported mortality rates after ESBL-E bacteremia in patients with hematologic malignancies range from 13%-45% (Table 2) [2,7,10-12,14-16]. The majority of studies note an increased mortality rate after ESBL-E bacteremia compared to non-ESBL-E bacteremias in this population [2,7,10,11].…”
Section: Extended-spectrum β-Lactamase-producing Enterobacteriaceae (mentioning
confidence: 99%
“…Reported mortality rates after ESBL-E bacteremia in patients with hematologic malignancies range from 13%-45% (Table 2) [2,7,10-12,14-16]. The majority of studies note an increased mortality rate after ESBL-E bacteremia compared to non-ESBL-E bacteremias in this population [2,7,10,11].…”
Section: Extended-spectrum β-Lactamase-producing Enterobacteriaceae (mentioning
confidence: 99%
“…In a report from Korea, 44% of E. coli bacteremias in HSCT recipients were ESBL producers and having an HSCT was a risk factor for ESBL‐E bacteremia . HSCT centers from Italy and Turkey reported that 18% and 23%, respectively, of E. coli bloodstream isolates and 86% and 22%, respectively, of K. pneumoniae bloodstream isolates were ESBL‐producing strains . At our own HSCT center in New York City (NYC), 29 of 89 (33%) E. coli bloodstream isolates from 2011 to 2016 had a phenotypic profile suggestive of ESBL production (ceftriaxone‐resistant, meropenem‐susceptible).…”
Section: Esbl‐producing Enterobacteriaceae (Esbl‐e)mentioning
confidence: 98%
“…ESBLs are enzymes that are capable of hydrolyzing penicillins, monobactams, and extended‐spectrum cephalosporins . Multiple reports from oncology centers in North America, Europe, and Asia have identified ESBL prevalence rates of 17%‐37% among bloodstream isolates of Enterobacteriaceae from patients with hematologic malignancies (Table ). Not only did these reports demonstrate a high prevalence of ESBL‐E in this population, but many also reported higher mortality rates associated with ESBL‐E bacteremia compared to bacteremia caused by non‐ESBL‐producing Enterobacteriaceae.…”
Section: Esbl‐producing Enterobacteriaceae (Esbl‐e)mentioning
confidence: 99%
“…Observa-se, nas publicações científicas, em termos de complicações e cuidados de enfermagem no pós-TCTH, maior enfoque no período de internação (13)(14) e não no período de cuidado ambulatorial. Ressalta-se ainda lacuna nessas publicações, aborda-se usualmente crianças e adultos simultaneamente (15)(16) , com poucos estudos voltados às especificidades pediátricas.…”
Section: Introdução Métodounclassified